Generasi Z, Pustakawan, dan Vita Activa Kepustakawanan - Kamil, Rusdan; Laksmi (BACA: Jurnal Dokumentasi dan Informasi, 2023)
ABSTRACT  Currently, generation Z has become one of the active groups in the world of librarianship. Vita Activa, or active life, refers to human life actively engaged with the material world, including social, cultural, and political affairs. In his book “Cerita Tentang Pustakawan dan Kepustakawanan” (CTPK), Sudarsono argues that librarianship should go beyond administrative tasks in collecting and storing books. This research employs Critical Discourse Analysis (CDA) method developed by Fairclough, with a focus on examining the content of librarianship in the book "CTKP" through the lens of Hannah Arendt's Vita Activa theory, encompassing labor, work, and action. Findings at the microstructural level reveal that the book serves as a source of information and inspiration within the discursive material. At the mesostructural level, discourse about the ideal librarianship can motivate librarians who may be feeling pessimistic about their profession, especially those from generation Z. Sudarsono reflects on his personal experiences to assist readers, particularly generation Z, as mentioned in his book. On the macrostructural level, Sudarsono portrays librarianship as a service-oriented profession that requires active efforts in overcoming bureaucratic and institutional political obstacles. In conclusion, librarianship is depicted as a metaphor for life's journey, presenting negative emotional experiences and the author's hopes for young aspiring librarians, including those from generation Z, which are openly interpreted as part of the discursive material. Future research can analyze how generation Z librarians respond to the findings of this study in their daily practices in the field of librarianship.   ABSTRAK Saat ini generasi Z menjadi salah satu kelompok yang aktif dalam dunia kepustakawanan. Kehidupan aktif (Vita Activa) sendiri adalah kehidupan manusia yang terlibat aktif dengan dunia material baik dalam urusan sosial, budaya maupun politik. Dalam karyanya buku Cerita Tentang Pustakawan dan Kepustakawanan (CTKP), Sudarsono berpendapat bahwa kepustakawanan harus melampaui tugas administratif dalam pengumpulan dan penyimpanan pustaka. Penelitian dilakukan menggunakan metode Analisis Wacana Kritis (Critical Discourse Analysis / CDA) yang dikembangkan oleh Fairclough, berfokus untuk mengkaji materi kepustakawanan dalam buku CTKP melalui lensa teori Vita activa Hannah Arendt, mencakup kerja, karya, dan tindakan. Temuan pada tingkat analisis mikrostruktural, buku ini sebagai sumber informasi dan inspirasi sebagai bagian dari materi diskursif, pada tingkat analisis mesostruktural, wacana tentang kepustakawanan ideal dapat memotivasi pustakawan yang merasa pesimis dalam profesi mereka. Sudarsono mencerminkan pengalaman pribadinya untuk membantu pembaca, terutama generasi Z, yang disebutkan dalam bukunya. Secara makrostruktural, Sudarsono menggambarkan kepustakawanan sebagai pekerjaan pelayanan yang memerlukan upaya aktif dalam mengatasi hambatan birokrasi dan politik institusi. Kesimpulannya, kepustakawanan digambarkan sebagai metafora perjalanan hidup dengan menghadirkan pengalaman emosi negatif dan harapan penulis terhadap calon pustakawan muda termasuk pustakawan generasi Z yang dimaknai secara terbuka sebagai materi diskursif. Penelitian masa depan dapat menganalisis bagaimana pustakawan generasi Z merespons temuan dari penelitian ini dalam praktik sehari-hari mereka di dunia kepustakawanan.